MEDIA PEMBELAJARAN TEMATIK â€œPAPAN ACAK KATAâ€ UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS VB SD N 2 PADOKAN - Sukadari Sukadari (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2019)
AbstractThis study aims to determine the effectiveness of the development of concrete-based learning media "RANDOM WORD BOARD" on the thematic learning system class VBSDN 2 Padokan. The study was conducted based on the current curriculum that uses the concept of thematic learning and which sometimes makes students feel difficult in finding the core subject matter delivered by teacher. This research is a development research. The method used is descriptive method. Data collection techniques using interview techniques, observation and documentation. The results of this development study indicate that learning media products are feasible to use. This is based on the results of the many samples who tried the RANDOM OF RANDOM BOARD learning media that can receive learning materials well. The main benefit obtained by students is the RANDOM BOARD OF WORDS learning media makes it easier for students to understand the thematic learning material delivered by the teacher.Keywords: Development, Learning Media, RANDOM BOARD OF WORDS, Thematic